A STUDY ON INFLUENCE OF USING DAM RESERVOIR WATER AS THERMAL RESOURCES UPON THE WATER QUALITY OF THE RESERVOIR - KAWAYOKE, Takahiro; SAITO, Takahiro; FUKUJU, Shinya; NONAKA, Akihiko (Proceedings of the Symposium on Global Environment, 1998)
In this study, the performance of water quality of a dam reservoir near a city area was predicted by the one-dimensional multi-layer model for the case where water of a reservoir was hypothetically utilized as thermal resources for a district heat supply project. Also investigated was the degree of the influence against water environment. As a result, there was no tendency that the multiplication of algae was higher by the hot drainage in summer time with the presently set up scale of using water. Overall, it can be concluded that a current level of water quality will be maintained under such a using condition. Based on these results, the authors investigated ways to utilize thermal energy of water and to improve water environment of dam reservoir in order to promote using water in a reservoir as thermal resources.